SHARING Choices: A Pilot Study to Engage Family in Advance Care Planning of Older Adults With and Without Cognitive Impairment in the Primary Care Context. (November 2021) - Wolff, Jennifer L.; Scerpella, Danny; Cockey, Kimberly; Hussain, Naaz; Funkhouser, Tara; Echavarria, Diane; Aufill, Jennifer; Guo, Amy; Sloan, Danetta H.; Dy, Sydney M.; Smith, Kelly M.; ,
Context: Few advance care planning (ACP) interventions proactively engage family or address the needs of older adults with and without cognitive impairment in the primary care context. Objectives: To pilot a multicomponent intervention involving: an introductory letter describing a new clinic initiative and inviting patients to complete a patient-family pre-visit agenda-setting checklist, share their electronic health information with family, and talk about their wishes for future care with a trained ACP facilitator (SHARING Choices). Methods: SHARING Choices was delivered to 40 patient-family dyads from 3 primary care clinics. Facilitators completed post-ACP reports. Patient and family participants completed baseline and 6-week surveys. Results: Patients were on average 75 years (range 65-90). Family were spouses (85.0%) or adult children (15.0%). At 6 weeks, nearly half of dyads participated in ACP conversations (n = 19) or used the agenda-setting checklist (n = 17), one-third (n = 13) registered family to access the patient's portal account, and most (n = 28) provided the primary care team with a new or previously completed advance directive. Of 12 patients who screened positive for cognitive impairment, 9 completed ACP conversations and 10 provided the clinic with an advance directive. ACP engagement, measured on a 4-point scale, was comparatively lower at baseline and 6 weeks among family (3.05 and 3.19) than patients (3.56 and 3.54). Patients remarked that SHARING Choices clarified communication and preferences while family reported a better understanding of their role in ACP and communication. Conclusion: SHARING Choices was acceptable among older adults with and without cognitive impairment and may increase advance directive completion.